Therapeutic effect and safety of curcumin in women with PCOS: A systematic review and meta-analysis - Shen, Wenjuan; Qu, Yangfan; Jiang, Huan; Wang, Hongwei; Pan, Yujia; Zhang, Yuehui; Wu, Xiaoke; Han, Yanhua; Zhang, Yang (Frontiers in Endocrinology, 2022)
Objective: This study aimed to evaluate the efficacy and safety of curcumin in the treatment of PCOS. Methods: Chinese databases (Chinese National Knowledge Infrastructure, China Biology Medicine Databases, VIP database, Wanfang Database, and Chinese Clinical Trial Registry) and English databases (PubMed, Web of Science, Embase, Cochrane Library, Scopus and Clinical trials) were thoroughly investigated through screening randomized controlled trials on curcumin in PCOS published from the date of inception to May 2022. Standardized data search and abstraction were conducted following the preferred reporting items for systematic reviews and meta-analysis (PRISMA) statement. Quantitative and qualitative analyses were performed. Heterogeneity was assessed using I2 statistics. Results: A total of 447 patients from seven randomized controlled trials were included in the meta‐analysis. Results showed that the ingestion of curcumin decreased body mass index (WMD -0.267, 95% CI -0.450 to -0.084, P = 0.004, I2 = 0.0%), fasting plasma glucose (WMD -3.618, 95% CI -5.165 to -2.071, P < 0.001, I2 = 20.4%), insulin (WMD -1.834, 95% CI -2.701 to -0.968, P < 0.001, I2 = 8.4%), homeostatic model assessment for insulin resistance (WMD -0.565, 95% CI -0.779 to -0.351, P < 0.001, I2 = 0.0%), total cholesterol (WMD -15.591, 95% CI -27.908 to -3.273, P = 0.013, I2 = 68.9%), C-reactive protein (WMD -0.785, 95% CI -1.553 to -0.017, P = 0.045, I2 = 23.9%), and increased the quantitative insulin sensitivity check index (WMD 0.011, 95% CI 0.005 to 0.017, P = 0.001, I2 = 39.6%). As for safety, the treatment group did not cause signiﬁcant adverse reactions than that in the control group. Conclusion: In light of presented findings, curcumin has beneficial effects on serum markers of inflammation, weight loss and glucose and lipid metabolism in patients with PCOS. The incidence of adverse reactions does not increase with the application of curcumin. However, a larger, more definitive study is needed to further investigate these results.